2016
DOI: 10.1103/physrevd.94.086004
|View full text |Cite
|
Sign up to set email alerts
|

Engineering holographic phase diagrams

Abstract: By introducing interacting scalar fields, we tried to engineer physically motivated holographic phase diagrams which may be interesting in the context of various known condensed matter systems. We introduce an additional scalar field in the bulk which provides a tunable parameter in the boundary theory. By exploiting the way the tuning parameter changes the effective masses of the bulk interacting scalar fields, desired phase diagrams can be engineered for the boundary order parameters dual to those scalar fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Since many high temperature superconductors are believed to be strongly coupled, the holographic tool has also been used to mimic the phase diagram of high Tc superconductors [10,11]. In these studies, an important issue is to deal with systems with multiple order parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Since many high temperature superconductors are believed to be strongly coupled, the holographic tool has also been used to mimic the phase diagram of high Tc superconductors [10,11]. In these studies, an important issue is to deal with systems with multiple order parameters.…”
Section: Introductionmentioning
confidence: 99%
“…(6), (7), (19) and aforementioned form factors Eqs. (20) and (21) into Eq. (5) and using the so-called covariant instantaneous approximation [35], p l = q l (which ensures that the BS equation is still covariant after this approximation).…”
Section: The Bethe-salpeter Formalism For Bk Systemmentioning
confidence: 99%
“…In Refs. [19,20], the authors showed that X(5568) or X(5616) could not be assigned to be an BK or B * K molecular state. X(5568) is also disfavored as a P -wave coupled-channel scattering molecule involving the states B s π, B * s π, BK and B * K in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the technique of realizing various phase transition order parameters in holographic superconductor models have been applied to the study the competition and coexistence of multiple order parameters [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. The authors of ref.…”
Section: Introductionmentioning
confidence: 99%